2019
DOI: 10.1002/cncy.22137
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemistry for predictive biomarker testing in lung cancer cytology

Abstract: With an escalating number of predictive biomarkers emerging in non-small cell lung carcinoma (NSCLC), immunohistochemistry (IHC) is being used as a rapid and cost-effective tool for the screening and detection of many of these markers.In particular, robust IHC assays performed on formalin-fixed, paraffin-embedded (FFPE) tumor tissue are widely used as surrogate markers for ALK and ROS1 rearrangements and for detecting programmed death ligand 1 (PD-L1) expression in patients with advanced NSCLC; in addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 99 publications
(251 reference statements)
5
119
1
Order By: Relevance
“…ICC, especially on alcohol‐fixed cytology preparations, may demonstrate discordant staining results with IHC protocols that are standardized for formalin‐fixed tissue and requires careful validation . Alcohol‐fixed smears and liquid‐based cytology preparations have been previously used for INSM1 ICC in a small study on pancreatic NE tumors in which all 14 NE tumors of different grades demonstrated strong positivity for INSM1, a finding that is concordant with the 100% sensitivities reported with INSM1 IHC for pancreatic NE tumors in other studies .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…ICC, especially on alcohol‐fixed cytology preparations, may demonstrate discordant staining results with IHC protocols that are standardized for formalin‐fixed tissue and requires careful validation . Alcohol‐fixed smears and liquid‐based cytology preparations have been previously used for INSM1 ICC in a small study on pancreatic NE tumors in which all 14 NE tumors of different grades demonstrated strong positivity for INSM1, a finding that is concordant with the 100% sensitivities reported with INSM1 IHC for pancreatic NE tumors in other studies .…”
Section: Discussionsupporting
confidence: 68%
“…3,5,6,[8][9][10][11] ICC, especially on alcohol-fixed cytology preparations, may demonstrate discordant staining results with IHC protocols that are standardized for formalin-fixed tissue and requires careful validation. 18 Alcohol-fixed smears and liquid-based cytology preparations have been previously used for INSM1 ICC in a small study on pancreatic NE tumors in which all 14 NE tumors of different grades demonstrated strong positivity for INSM1, 16 a finding that is concordant with the 100% sensitivities reported with INSM1 IHC for pancreatic NE tumors in other studies. 6 Among previous ICC studies on SCLC, Rodriguez et al 11 and Doxtader and Mukhopadhyay 5 both reported 100% concordance between IHC and ICC in 4 and 20 paired samples, respectively, in which the former performed ICC on formalin-fixed CBs and the latter on PreserveCyt-fixed Cellient CBs.…”
Section: Insm1 On Cytology Smears/nakra Et Alsupporting
confidence: 59%
“…A discussion of all of these variables would be beyond the scope of this review, but a detailed description of all factors influencing immunocytochemistry testing can be found in the expert opinion of the International Association for the Study of Lung Cancer Pathology Committee. 64 The major advantage of IHC and ISH is that all fusion events can be detected independently from the fusion partner. Both methods are currently standard in most pathology laboratories and require little technical expertise.…”
Section: Ihcmentioning
confidence: 99%
“…In this issue of Cancer Cytopathology , Jain et al, as part of the International Association for the Study of Lung Cancer (IASLC) Pathology Committee, perform a deep dive into the topic of immunocytochemistry (ICC) for predictive biomarker testing in NSCLC. This work serves as a complementary piece to the recently published review by the same group covering the best practice recommendations for IHC in the diagnostic workup of lung cancer .…”
Section: Current Immunohistochemistry Uses For Biomarker Testing In Nmentioning
confidence: 99%
“…Given the backdrop of rapid change in thoracic oncology and resulting increased testing complexity in this era of personalized medicine, it behooves the cytopathologist to actively participate in a process that has been described as “personalized sample management.” The tumor cell quality, quantity, and purity can greatly vary from specimen to specimen. When considering relevant clinicopathologic features as well as the medical urgency dictated by the clinical status of the patient, the cytopathologist as part of the clinical care team is best situated to enter into discussions with the oncologist to decide if and how to deviate from standard testing algorithms, for instance deciding when to use focused biomarker ICC testing as outlined in the accompanying paper by Jain et al…”
Section: Current Immunohistochemistry Uses For Biomarker Testing In Nmentioning
confidence: 99%